The effect of using a portfolio of comparable firms on the accuracy of the price-earnings valuation method - Chua, Kok Hua (2009)
The Price-Earnings (P/E) Valuation Method estimates a firm's stock price as the product of its earnings and the P/E multiple determined from a set of comparable firms. This paper studies empirically the accuracy of the P/E valuation method when comparable firms are selected on the basis of the market, industry, total asset, earnings growth, beta, individually and in pairs. The effect of firm size on the valuation accuracy was also examined.